Analisis Strategi Pemasaran 4P (Product, Price, Place, and Promotion) Terhadap Pencapaian Target Seat Keberangkatan Umroh: Pendekatan SWOT Pada PT Berkah Utama Travel Bengkulu - Adelia Amanda; Yosy Arisandi; Kustin Hartini (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the 4P marketing strategy (product, price, place, promotion) towards achieving the target of Umrah departure seats: the SWOT approach at PT. Berkah Utama Tour & Travel Bengkulu. This type of research is field research uses a qualitative approach. Data analysis techniques use SWOT analysis. Data were collected through interviews, observations, and documentation. The results of the study indicate that the strategy used by PT. Berkah Utama Tour & Travel Bengkulu is quite effective in achieving the target of Umrah departure seats. Products with various choices, competitive prices, strategic locations, and online and offline promotions. The results of the internal factors SWOT analysis of PT. Berkah Utama Tour & Travel Bengkulu possesses several strengths, including legality, the KSA team, an extensive branch network, and ownership by six partners. and a 13-day flagship package. However, there are weaknesses in price perception and the package options. External factors of opportunity have good relationships with pilgrims, and it is one of the companies that is quite developed. Threats faced include the pilgrims' congregation still lacking knowledge regarding key factors to consider when choosing a travel agency, as well as intense competition among Umrah travel agencies.